Pengelompokan Peserta Didik - Konitatillah, Maulida Putri; Sekarsari, Nasya Ayu; Zafiena, Nayla Haris; Erlangga, Philip; Prestiadi, Dedi (Universitas Negeri Malang, 2025)
Grouping is the grouping of learners based on their characteristics. Such characteristics need to be classified, so that they are in the same condition. The existence of the same conditions can facilitate the provision of the same services. Therefore, grouping is commonly referred to as classification. The focus of this research is the rationale for grouping students, the purpose and function of grouping students, types of grouping and challenges in grouping students. Pengelompokan atau grouping adalah pengelompokan peserta didik berdasarkan karakteristik-karakteristiknya. Karakteristik demikian perlu digolongkan, agar mereka berada dalam kondisi yang sama. Adanya kondisi yang sama ini bisa memudahkan pemberian layanan yang sama. Oleh karena itu, pengelompokan (grouping) ini lazim dengan istilah pengklasifikasian (classification). Fokus penelitian ini adalah rasional pengelompokan peserta didik, tujuan dan fungsi pengelompokan peserta didik, jenis pengelompokan dan tantangan dalam pengelompokan peserta didik